2008
DOI: 10.1007/bf03021433
|View full text |Cite
|
Sign up to set email alerts
|

Effets cardioprotecteurs du propofol dans des cœurs ischémiques puis reperfusés isolés chez le cobaye: rôle des canaux KATP et du GSK GSK-3β

Abstract: reports of original investigations 595 CAN J ANESTH 55: 9 www.cja-jca.org September, 2008 Purpose: Propofol exerts cardioprotective effects, but the involved mechanisms remain obscure. The present study examines the cardioprotective effects of propofol and its role in cardiac function, including its effect on K ATP channel opening and the inhibition of GSK-3β activity in ischemia-reperfused hearts.Methods: Ischemia-reperfusion (I/R) was produced in isolated guinea pig hearts by stopping coronary perfusion for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…Inactivation of GSK-3 β may result in a decrease of proinflammatory cytokines [35]. A recent study has also shown that GSK-3 β inactivation was involved in a propofol-induced protective effect against IR injury in an isolated guinea pig heart [36]. Our data showed that the changes in p-GSK-3 β paralleled the alterations of serum ALT activity and IL-1 β expression.…”
Section: Discussionsupporting
confidence: 66%
“…Inactivation of GSK-3 β may result in a decrease of proinflammatory cytokines [35]. A recent study has also shown that GSK-3 β inactivation was involved in a propofol-induced protective effect against IR injury in an isolated guinea pig heart [36]. Our data showed that the changes in p-GSK-3 β paralleled the alterations of serum ALT activity and IL-1 β expression.…”
Section: Discussionsupporting
confidence: 66%
“…Several mechanisms have been proposed to explain the cardioprotective properties of propofol which include increased phosphorylation of phospho-glycogen-synthase kinase (GSK-3 β ) [36], inhibition of MPTP opening [11], reduced lipid peroxidation and lowered inflammation [37], and modulation of calcium channel activity [17]. The reduction in levels of cytosolic calcium is unlikely to be involved in cardioprotection in immature heart.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms of propofol action, including free radical scavenging and activation of anti-apoptotic pathway, have been proposed [25]. However, in recent years other targets of propofol cardioprotection such as protein kinase C [26], glycogen synthase kinase 3β [27] and nitric oxide synthase [28] have been suggested. Our results suggest that mitochondria are targets for propofol-induced cardioprotection.…”
Section: Discussionmentioning
confidence: 99%